Development of expressed sequence tags (ESTs) from the brain tissue of snowtrout Schizothorax richardsonii (Gray, 1832) (Family Cyprinidae) and its preliminary annotation - Barat, Ashoktaru; Goel, Chirag; K. Sahoo, Prabhati; Rao, A. R. (Indian Journal of Fisheries, 2014)
The snowtrout (Schizothorax richardsonii) is an economically important fish in the north-east Himalayan region. However, genomic research on this species is still in its infancy, and genomic resources are largely unavailable. The objective of this study was to generate expressed sequence tags (ESTs) from a brain complementary DNA (cDNA) library and to identify the genes. A total of 1031 ESTs were sequenced, from which 73 contigs and 411 singletons were identified. BLAST homology analysis indicated that only 9.3% of these ESTs were homologues of known genes while the remaining 90.7% appeared to be novel sequences. Based on sequence similarities, 45 putative genes were identified that encodes stress proteins, enzymes and signal transduction regulators. Our study thus, provides a collection of novel transcripts and a partial annotation of genes that are expressed in brain tissue of the snowtrout species, S. richardsonii.